Prospecção dos inibidores de fosfolipases A2 das classes alfa e gama (PLI e PLI) endógenos no plasma de serpentes Crotalidae brasileiras: caracterização molecular e propriedades biológicas - Maria Inacia Estevao Costa (2008)
The presence of phospholipase A2 (PLA2) inhibitors in the blood plasma of snakes has been reported by several authors. These inhibitors are, presently, classified in three structural classes named alfa, beta and gamma. Alfa-inhibitors contain a domain similar to the carbohydrate recognition domain (CRD) of C-type lectins, whereas beta-inhibitors display leucine-rich repeats (LRR) such as those present in the human alpha2- macroglobulin. In the gamma-class members, in turn, the cystein pattern resembles that found in the uroquinase-type plasminogen activator receptor (u-PAR). In the present study we investigated the presence of mRNA codifying for alfa- and gamma-PLA2 inhibitors (PLIs) in the liver tissue of of six Brazilian snake species in the genus Bothrops (B. alternatus, B. erythromelas, B. jararaca, B. jararacussu, B. moojeni and B. neuwiedi) besides Lachesis muta and Crotalus durissus terrificus, by RT-PCR. DNA amplification was performed in the presence of primers designed based on PLIs already published in the literature (an alpha-PLI from Agkistrodon blomhoffii siniticus and a gamma-PLI from C. d. terrificus). The amplification products were cloned in TA-kind plasmid vector and a number of putative positive clones was confirmed by PCR. The DNAs of a minimum of four and two positive clones for alfa- and gamma- PLIs, respectively, were completely sequenced. The nucleotide sequences as well as the deduced primary sequences obtained were aligned with known PLIs looking for homology. A detailed analysis of each novel PLI-homologous protein was performed using bioinformatics tools. Phylogenetic trees were derived for the alpha- and gamma-PLIs from Brazilian snakes described, so far, and the tridimensional structure of an alpha-PLI (from L. muta) was modelled by homology. The obtention of a representative recombinant protein alpha-PLI (in procariote) are described.